The effect of Re and Ru on γ/γ′ microstructure, γ-solid solution strengthening and creep strength in nickel-base superalloys - Heckl, Astrid; Neumeier, Steffen; Göken, Mathias; Singer, Robert (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2011)
A new in-house designed series of Ni based superalloys with stepwise increased Re and Ru additions has been investigated, to systematically determine the influence of Re and Ru on γ/γ′-microstructure and high temperature creep properties. Improved creep resistance and thus also a higher alloy temperature capability of up to 87. K/at.% was found for additions of Re. Additions of Ru revealed a lower temperature capability improvement of up to 38. K/at.% for low Re-containing second generation alloys. However, in third and fourth generation alloys with higher Re-contents, no significant influence of Ru on creep rupture strength was observed. The creep properties are discussed with respect to the γ′-volume fraction, γ′-size and γ′-coarsening rate, as well as the γ/γ′-lattice misfit and the γ/γ′ partitioning coefficient of the different Re and Ru containing alloys. The presented data shows, that these microstructure parameters are strongly influenced by additions of Re, but only marginally by additions of Ru. A further influence on creep rupture strength is given by the solid solution hardening of the γ-matrix, which is discussed based on solid solution hardener concentrations either experimentally derived or calculated from ThermoCalc data. © 2011 Elsevier B.
Keywords: γ′-Coarsening rate; γ′-Size; γ′-Volume fraction; γ/γ′-Distribution coefficient; Creep resistance; Solid solution strengthening

Verification of a commercial CALPHAD database for Re and Ru containing nickel-base superalloys - Rettig, Ralf; Heckl, Astrid; Neumeier, Steffen; Pyczak, F.; Göken, Mathias; Singer, Robert (Defect and Diffusion Forum, 2009)
The addition of rhenium and ruthenium to single crystal nickel-base superalloys improves the high-temperature properties of the alloys. In this work the applicability of the database TTNi7 (ThermoTech Ltd, UK) for developing 4 generation single crystal superalloys containing rhenium (Re) and ruthenium (Ru) was investigated. We systematically compared experimentally determined alloy properties to the predictions of ThermoCalc with the database TTNi7. The investigated properties were liquidus, solidus and γ′ solvus temperature as well as incipient melting point and segregation. Calculations were based on thermodynamic principles with the assumption of either equilibrium or Scheil-Gulliver conditions, i.e. no diffusion in the solid and complete diffusion in the liquid. Furthermore the composition of the γ and the γ′ phase of a Re- and Ru-containing superalloy was measured and compared to calculations. Our results show that the database is capable of simulating general trends of 4 generation superalloys up to 6 weight percent (wt.-%) Re and 6 wt.-% Ru. The present work shows that Scheil-Gulliver calculations can only be used as a first approximation for nickel-base superalloys. © (2009) Trans Tech Publication
Keywords: CALPHAD; Database; Modelling; Rhenium; Ruthenium; Scheil-Gulliver; Single crystal; Superalloys; ThermoCalc